Non-coding RNAs as Putative Biomarkers of Cancer-Associated Cachexia - Donzelli, Sara; Farneti, Alessia; Marucci, Laura; Ganci, Federica; Sacconi, Andrea; Strano, Sabrina; Sanguineti, Giuseppe; Blandino, Giovanni (Frontiers in Cell and Developmental Biology, 2020)
Cachexia is a complex metabolic syndrome that determines a severe body weight loss characterized by a marked reduction in muscle mass. About 80% of patients with advanced cancer develop cachexia due to both the tumor itself and cancer treatment (radiotherapy and/or chemotherapy), which is associated to a worse prognosis. Despite its clinical relevance, this syndrome is still under-diagnosed and it lacks effective treatments. Radio-chemotherapy treatment is essential in patients with advanced head and neck cancers (HNSCC). Although this treatment has improved patients’ life expectancy, it has also dramatically increased their need for assistance and support. The management of adverse symptoms, including cachexia, is of great importance in order to avoid delays in therapy, reduction of dosages and hospitalizations. MicroRNAs (miRNAs) are small non-coding RNA molecules, which have emerged as powerful biomarkers in stratifying human cancers. Due to their high stability in body fluids, miRNAs might be excellent non-invasive biomarkers for the early detection and follow-up of cancer patients. Here, we will summarize the current knowledge and debate the strong need to identify circulating biomarkers for the early diagnosis of cachexia. We will propose circulating non-coding RNAs as biomarkers for detecting early cachexia and implementing specific treatment. We will also discuss the potential use of circulating miRNAs as biomarkers of cachexia in HNSCC patients’ blood samples collected before and after radio-chemotherapy treatment. Our intent is to pave the way to the identification of specific circulating miRNAs associated to cachexia occurrence and to the design of specific interventions aimed at improving the quality of life of cancer patients.